PENGARUH SUBSTITUSI TEPUNG IKAN LELE TERHADAP PEMBUATAN COOKIES BEBAS GLUTEN DAN KASEIN SEBAGAI ALTERNATIF JAJANAN ANAK AUTISM SPECTRUM DISORDER [Effect of Catfish Flour Substitution towards Gluten-Free and Casein-Free Cookies as an Alternative Snack for Children with Autism Spectrum Disorder] - Aliffah Nurria Nastiti; Juliana Christyaningsih (Universitas Airlangga, 2019)
Children with Autism Spectrum Disorder (ASD) have digestive disorders, therefore their diet should be gluten-free and casein-free. Gluten-free and casein-free foods tend to be low in protein. ASD children who apply a gluten-free diet and casein have a lower calcium intake and low in bone density. Catfish flour with high protein and calcium content were expected to increase the nutritional value (protein and calcium) of cookies which gluten-free and casein-free. This study was aimed to determine the effect of catfish flour substitution towards acceptance and nutritional value of gluten and casein free cookies as an alternative snack for ASD children. This study was experimental research with Completely Randomized Design. Panelists of this study were children with ASD (4-6 years) and their parents as many as 40 people. There were 4 formulas in this study, F0 was control, and 3 substitution formulas. Percentage of Flour substitution were, F2 (2%: 2%); F3 (4%: 4%); and F5 (6%: 4%). Kruskal Wallis test showed no significant difference in the level on acceptance level in taste and aroma between F0, F3, and F5. The acceptability and nutritional value's ranking showed the best formula was F5. 100 grams of F5 cookies (protein: 6.75 g; calcium: 247.51 mg) can fulfill 19% of the protein and 24.8% calcium of children RDA (4-6 years). Gluten-free and casein-free cookies with catfish (Formula 5) with enough protein and high calcium can be an alternative snack for ASD children.